1996
DOI: 10.1111/j.1398-9995.1996.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediator release is altered in immunotherapy‐treated patients: a 4‐ear study

Abstract: In recent years, it has been possible to demonstrate mediator release into the nasal secretion after nasal allergen challenge in patients with allergic rhinitis. Using the nasal provocation model, we determined whether the mediator release was altered in immunotherapy-treated patients. Seventeen grass-pollen-allergic patients were examined under controlled, reproducible conditions. Serial challenges with increasing doses of grass pollen produced increasing numbers of clinical symptoms and release of mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…A number of observations indicate that allergen-specific IgG may play an important role in the mechanism of successful allergy vaccination: first, IgG compete with IgE for binding to the allergen reducing histamine release from mast cells and basophils in vitro by interfering with the cross-linking of receptor-bound IgE (17). Second, the allergen-specific IgG disturb allergen-IgE complexes, which bind to CD23, i.e., the low affinity IgE receptor, on APCs facilitating Ag presentation to T cells (18); and third, IgG may mediate inhibition of downstream Fc⑀RI signaling in human basophils (19).…”
mentioning
confidence: 99%
“…A number of observations indicate that allergen-specific IgG may play an important role in the mechanism of successful allergy vaccination: first, IgG compete with IgE for binding to the allergen reducing histamine release from mast cells and basophils in vitro by interfering with the cross-linking of receptor-bound IgE (17). Second, the allergen-specific IgG disturb allergen-IgE complexes, which bind to CD23, i.e., the low affinity IgE receptor, on APCs facilitating Ag presentation to T cells (18); and third, IgG may mediate inhibition of downstream Fc⑀RI signaling in human basophils (19).…”
mentioning
confidence: 99%
“…Interestingly Dokic et al . in their study demonstrated that IgG4 could inhibiting release of mediators [27]. IgG4 levels correlated with the TAME-enzyme activity, which is closely related with bradykinin formation ( r = 0.85; p < 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…Taka interpretacja wyników poparta jest wynikami badań podstawowych, które wskazują na istotną rolę IgG4 w hamowaniu wydzielania mediatorów. W badaniach Dokica [32] stężenie IgG4 korelowało z aktywnością TAME (r = 0,85; p < 0,01). Nieco odmienne wyniki uzyskali w swych badaniach Creticos i wsp.…”
Section: Omówienieunclassified
“…Publikowane w piśmiennictwie świa-towym badania nad neuropeptydami u ludzi ze względu na trudności metodologiczne (próby prowokacyjne, oznaczenia peptydów w wydzielinie nosowej) i koszty również opierają się na wynikach uzyskanych w małych grupach obejmują-cych 6-13 chorych [9,15,32].…”
Section: Omówienieunclassified